Nineteenth-Century British Music Studies - Zon, Bennett (Aldershot Ashgate, 1999)
Vol. 1 comprises fifteen papers given at the first conference of the Society for the Study of Music in Nineteenth-Century Britain, held at the University of Hull in July 1997. As is inevitably the case with such collections, the papers reproduced here vary in quality and do not form a series linked by a common thread or perspective beyond that of their geographical and temporal focus. Nonetheless, Bennett Zon's enterprise in organizing the conference (which has been followed by two more held at the University of Durham) and publishing this volume deserves recognition and praise. As Nicholas Temperley notes in his foreword, the cause of British music has been transformed since he started his own doctoral work in the fifties, when Thurston Dart thought he was mad and "more moderate advisers thought I was indulging in a gesture of rebellion which would cost me my career" (p. xvii).The papers cover a wide variety of subjects, from the overarching (Temperley's keynote address, titled "Xenophilia in British Musical History") to the highly specific (Allan Atlas's paper on concertina sales in winter 1851), although this is very much a volume on musical life in Britain rather than British music. Several papers may be cited as informative and stimulating. Temperley's address poses essential questions about why the British seemed so inordinately fond of foreign music and musicians in the nineteenth century and when the "Renaissance" really started. His (inevitably) brief answers give food for thought about two of the most intractable issues faced by scholars in this area. Other papers falling into this category are those by Zon ("History, Historicism and the Sublime Analogy"), David Golby ("Violin Pedagogy in England during the First Half of the Nineteenth Century, or The Incompleat Tutor for the Violin"), and Simon McVeigh ("The Benefit Concert in Nineteenth-Century London: From 'Tax on the Nobility' to 'Monstrous Nuisance'"), all of which cover interesting areas and add to our understanding of British musical life. Golby, for example, demonstrates well how aspiring British violinists were faced with inadequate and unfocused tuition, a circumstance that led to an inevitable preference for foreign musicians and the complementary failure to improve matters at home; after all, why bother training people for a socially dubious profession when foreigners can be imported instead? McVeigh's paper deals with the ups and downs of the benefit concert and alludes similarly to the commercial pressures that drove much of British musical life and led concert promoters to pander to the whims of those commanding the highest fees and those holding the purse strings.Other papers worthy of attention are Jeremy Dibble's on Hubert Parry as historiographer, Trevor Herbert's on the Cyfartha Brass Band, Philip Olleson's on Samuel Wesley, Peter Horton's on Samuel Sebastian Wesley (the only chapter that deals directly with the music of a British composer), Stuart Campbell's on musical life in Glasgow in the 1870s, Caroline Wood's on musicmaking in Yorkshire, Barbara Mohn's on the personification of Christ in British oratorios, and Catherine Dale's on the emergence of a British analytical tradition (principally that of Donald Francis Tovey). These papers focus on very specific areas, and in many cases I would have found it useful if the authors had been able to expand somewhat further on the significance of their investigations. For example, Parry's historiographical writings reflect, as Dibble demonstrates, many of Parry's own aesthetic beliefs, and it would have been splendid to see, if only fleetingly, how Dibble believes these views might have influenced the ethos of the Royal...
Vol. 2: Sacred music; opera and oratorio; reception history; contemporary performance and analysis; the intersection of music and poetry; and music iconography: these are the areas explored in this volume derived from papers given at the second Music in Nineteenth-Century Britain conference, held at the University of Durham in 1999. They represent leading work which continues to discover and rediscover all aspects of musical life in nineteenth-century Britain.The volume opens with an in-depth examination of the Concert Life in Nineteenth-Century London Database and its progress in the last two years.Church music topics feature large - a fitting tribute to Durham's extraordinary ecclesiastical heritage. John Harper, Christopher Turner, Barra Boydell, Sally Drage, Brian Crosby and David Knight contribute a series of articles exploring the music practices of monasteries, convents, cathedrals, abbeys and the performance of psalmody in churches.Aspects of opera and oratorio, especially in relation to concepts of national identity, are covered in essays by Duncan Barker, Walter Clark and Jean Marie Hoover. The perception of the musical work and its relationship to performance is also dealt with, and forms the subject of articles by Robert Bledsoe, Sue Cole, Therese Ellsworth and Dorothy De Val.The concert programme and its influence upon performance receives treatment by Catherine Dale, who surveys the increasingly analytical content of nineteenth-century programme notes, whilst Jeremy Dibble and Peter Horton utilize modern analytical techniques to investigate British orchestral variations and the music of Samuel Wesley.The volume ends with an examination of the relationship between music and poetry with essays by Christopher Wilson and Michael Allis, and an iconographical study centring on the British Aesthetic Movement by Suzanne Fagence Cooper.
Vol. 3 is selected from papers given at the third biennial conference on Music in Nineteenth-Century Britain, this volume, in common with its two predecessors, reflects the interdisciplinary character of the topic. The introductory essay by Julian Rushton foregrounds some of the questions that are key to this area of study: what is the nineteenth century? what is British music? and did London influence the continent? The essays which follow are divided into broad thematic groups covering aspects of gender, church music, national identity, and local and national institutions. This collection illustrates that while nineteenth-century British music studies is still in its infancy as a field of research, it is one that is burgeoning and contributing to our understanding of British social and cultural life of the period.Contents: Introduction; Learning in London, Julian Rushton; Issues of gender: 'Leadership of fashion in musical thought': the importance of Rosa Newmarch in the context of turn-of-the-century British styles of music appreciation, Charlotte Purkis; Hym(n)ing: music and masculinity in the early Victorian church, Grant Olwage; The construction of a cultural icon: the case of Jenny Lind, George Biddlecombe; Church music: 'Hark an awful voice is sounding': redefining the English Catholic hymn repertory through The Westminster Hymnal of 1912, Thomas Muir; Ancient and modern in the work of Sir John Stainer, Nicholas Temperley; '...the highest point up to that time reached by the combination of Hebrew and Christian sentiment in music', Peter Horton; National identity: 'Unfurl the flag and Federate': flags as a representation of patriotism and nationalism in Australian Federation songs, 18801906, Peter Campbell; English national identity and the comic operas of Gilbert and Sullivan, Derek Scott; Singing the songs of Scotland: the German musician Johann Rupprecht Dürrner and musial life in 19th-century Edinburgh, Barbara Eichner; National and local institutions: Another string to his bow: the composer conducts, Duncan Barker; Vincent Novello and the Philharmonic Society of London, Fiona Palmer; The Oxford commemorations and 19th-century British festival culture, Susan Wollenberg; One equal music: the emergence of the Royal College of Music, Giles Brightwell; The family von Glehn, Valerie Langfield; Index
Keywords: 19th Century (1801-1900); Music history; United Kingdom